Program Edukasi Sexs Pada Lingkungan Anak Di Taman Baca Masyarakat Sukamulya - Syahalam, Ifah Rafifah; Indah, Rosiana Nurwa; Syam, Rifqi Zaeni Achmad (Halu Oleo University Kendari, 2023)
Sexs education for early childhood is now very urgent, so that its application becomes important in everyday life, both in formal, non-formal and informal forms. Even though the Community Reading Center can be a place to educate the public about sex education for children. This makes the purpose of this study to find out the implementation of sex education programs in children's environments through the Sukamulya Community Reading Center. The method used is descriptive qualitative. Data collection techniques through observation, interviews and documentation. There were three informants consisting of TBM administrators and parents of children. The results of the study show that the sex education program that has been carried out is through introducing the anatomy of the body, building positive habits, instilling the importance of protecting the organs, and getting children to dress according to their gender identity from an early age. This program is delivered through videos, pictures, songs and lectures that can be understood by children and parents. In addition, parents are also aware of their role as the first source of information about sex education for children.